The future of vocational education and training in a changing world - Pilz, Matthias [Herausgeber] (VS Verl. für Sozialwissenschaften, 2012)
"Around the world, vocational education and training (VET) is characterised by a number of common trends, including the increasing use of technology, the growing importance of information and communications systems, and changes to national demographics. Situated at the interface between the education and training system and employment, VET has a role in meeting these changes and contributing to the transition from education to employment, and providing the next generation with skills relevant to employment and the economic situation. This volume contains 30 chapters that represent a comprehensive overview of the current situation in VET, its strengths and weaknesses, and its prospects. Contributors from Canada, the USA, India, China, Japan and Korea, as well as from a number of European countries, focus on their national context and how it fits in to the bigger picture. The contributions combine theoretical discussions from various strands of VET research with evidence from country case studies and examples from current practice." (Verlag; BIBB-Doku)

Contents: Challenges and opportunities for technical and vocational education and training (TVET) in the United States (ZIRKLE; MARTIN); Youth apprenticeships in Canada: context, structures and apprentices' experiences (LEHMANN); Re-conceptualising vocational education: the transition from powerful to useful knowledge (CANNING); The transition from vocational to higher education from the perspective of higher education admission staff (ERTL; HAYWARD; MCLAUGHLIN; Development of TVET in China: issues and challenges / WEIPING SHI); Challenges of vocational education and career education in high schools in Japan: from the viewpoint of career-competency formation for transition (TERADA); Japan's public youth training programs, enterprise-sponsored training and the society of control (ITO); (Vocational) education and social inequality as Japanese society makes the transition to a 'global society' (ESWEIN); Trends and challenges of vocational education and training in Korea (SEUNG IL NA); Vocational education and training system (VET) in India (VENKATRAM); India's national skills development policy and implications for TVET and lifelong learning (SINGH); Challenges for evidence-based policy in European education and training (DUNKEL); Comparative analysis of VET curricula in Europe (FROMMBERGER; KRICHEWSKY); VET qualifications versus bachelor degrees?: recruitment at the intermediate qualification level: case studies from Germany, England and Switzerland (HIPPACH-SCHNEIDER; WEIGEL); Perceptions of science and technology in developed and developing countries: challenges for technical and vocational education and training (TVET) (BUNNING; KALISCH); Georg Kerschensteiner and the plea for work-oriented and vocational education: Germanys' educational debates in an industrial age (GONON); Reforming the VET system via national qualification frameworks?: a comparison of Germany and Austria (DEISSINGER); Vocational education and training in Poland during economic transition (KUREK; RACHWAL); Best for the bright?: the pros and cons of the new Danish apprenticeship model (AARKROG); Pre-vocational education in the curriculum and its teaching practice: a study of seven European countries (BERGER; PILZ); Are vocational qualifications vocational? (GALLACHER; INGRAM; REEVE); Apprenticeship: between theory and practice, school and workplace (RYAN); Demarcations between vocational and academic education and how to overcome them (RAUNER); Varieties of competence: European perspectives /(WINTERTON); Potentials for change in education and training through interactions between credit systems and qualifications frameworks (LEMOUILLOUR); Patterns of recruitment and induction in selected European countries: first results of a feasibility study (GROLLMANN; GEIBEN); Vocational education, poverty and power (CLEMENT); Bridging the gulf between the world of work and the world of learning: vocational education and training in comparative perspective (HOCKEL); International comparative research into vocational training: methods and approaches (PILZ).
Keywords: S 1.3 Berufliche Erstausbildung; G 1.3.2.2 Übergänge; G 1.2.3 Qualifikationsentwicklungen; T 1.5 International vergleichende Berufsbildungsforschung; I 2.3.2 Nordamerika; I 2.3.4 Asien; I 2.2 Europa; Berufsbildungssystem; Berufsbildung; Berufsausbildung; Berufseinmündung; Qualifikationsentwicklung; EU-Bildungspolitik; Vergleichende Berufsbildungsforschung; USA; Kanada; China; Japan; Südkorea; Indien; Polen; Österreich; Dänemark; Schweiz; Bundesrepublik Deutschland